Determinan Kebijakan Utang Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) - Romandona, Novia Ainur; Damayanti , Damayanti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
The purpose of this study is to show how profitability, company growth and company size affect debt policy in companies listed on the Jakarta Islamic Index. Companies listed on the Jakarta Islamic Index from 2018-2022 are the population in the study. There are 8 companies applied in the study. Purposive sampling is a method applied to select samples. Multiple linear regression is the procedure applied to analyse the data. The results of this study show that profitability has a positive and significant effect on debt policy, company growth has a negative and insignificant effect while company size has a positive and significant effect on debt policy. This study shows that profitability, firm growth, and firm size can explain the variation in debt policy with respect to companies listed on the Jakarta Islamic Index. The implication of the study is to help management formulate effective strategic decisions in managing debt.